Muslim-style Mausolea across Mongol Eurasia: Religious Syncretism, Architectural Mobility and Cultural Transformation - Blair, Sheila (Journal of the economic and social history of the Orient, 2019)
Abstract The first Mongol khans were buried in hidden graves, but later Mongols adopted the Muslim practice of building aboveground domed tombs. This essay examines three domed mausolea typical of the Muslim lands erected in the early to mid-14th century in different Mongol khanates—that built for the Ilkhan Öljeitü at Sultaniyya, a second for the Chaghadaid Buyan Quli Khan outside Bukhara, and a third anonymous tomb at Guyuan, Hebei, in the Yuan territories of north China—to show how different Mongol patrons interpreted the same form and funerary traditions associated with it.